The Impact of Using Artificial Intelligence Technologies on Crowd Management: A Field Study on Employees of the General Department of Crowd Management at the General Authority for the Affairs of the Grand Mosque and the Prophet’s Mosque in Makkah City - Taibah, Hassan AbdulQadir; Agili, Mohammad Omar; Khoj, Mohammad Hashem (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to examine the relationship between the use of artificial intelligence (AI) technologies—specifically surveillance, pattern recognition, data collection, and prediction—and crowd management at the Grand Mosque during Ramadan 1446 AH. It is based on a field study that draws on the perspectives of employees in the General Administration of Crowd Management at the General Authority for the Affairs of the Grand Mosque and the Prophet's Mosque in the city of Mecca. The theoretical framework of the research explores the concept of crowd management, the major challenges it faces, and the efforts made by the Kingdom of Saudi Arabia in this field. It also discusses the concept of artificial intelligence, its general applications, and its role in improving crowd management, while shedding light on the technical experiences employed in serving the pilgrims. The study further focuses on analyzing the impact of using AI technologies in regulating the flow of individuals and reducing the risks associated with overcrowding. It evaluates the effectiveness of these technologies in enhancing crowd management and offers proposals for developing future strategies for their implementation. The research includes an in-depth statistical analysis of the study’s findings, which contributes to reaching conclusions that support the future development of crowd management mechanisms at the Grand Mosque. The descriptive analytical method was used to examine the relationship between the use of artificial intelligence (AI) technologies and the effectiveness of crowd management at the Grand Mosque. A questionnaire was used as the primary tool for data collection, and a sample of 170 individuals was selected from a total study population of 300 employees. After statistically analyzing the collected data, the study reached several key findings. Most notably, there was a strong positive correlation (r = 0.75) between the use of AI technologies and crowd management.
Keywords: Artificial Intelligence; Crowd Management; Umrah; Al-Masjed Al-Haram; Makkah